2010
DOI: 10.1007/s12245-010-0201-0
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of tracheal intubation in an academic emergency department in Malaysia

Abstract: BackgroundAirway management is an important part of the management of the critically ill and injured patients in the Emergency Department (ED). Numerous studies from developed countries have demonstrated the competency of emergency doctors in intubation. To date there have been no published data on intubations performed in EDs in Malaysia.MethodsData on intubations from 7 August 2007 till 28 August 2008 were prospectively collected.ResultsThere were 228 intubations included in the study period. Cardiopulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…The full texts of 83 potentially eligible studies were obtained. After exclusion of all non‐relevant papers, 16 studies were included in the ‘ED‐All’ group . These reported a total of 42 081 airway encounters from 83 EDs, in 10 countries.…”
Section: Resultsmentioning
confidence: 99%
“…The full texts of 83 potentially eligible studies were obtained. After exclusion of all non‐relevant papers, 16 studies were included in the ‘ED‐All’ group . These reported a total of 42 081 airway encounters from 83 EDs, in 10 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from North America and Asia have demonstrated variable success and complication rates of RSI performed by emergency physicians. [10][11][12][13][14][15][16][17] There are limited data from the UK 4,5 so we reviewed our continuous registry of intubations in a large UK ED to characterise intubation sequences, success and complications. Our aims were to describe why, how and by whom ED patients were intubated, and to document the rates of successful intubation and complications related to the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The median age of subjects in this study is 51.5 years. Three other studies about intubation in the emergency room in Asian hospitals get lower median age (Fathil et al, 2010;Tam & Lau, 2001;Wong et al, 2004).…”
Section: Discussionmentioning
confidence: 95%